Citation success over time: Theory or empirics? - David W. Johnston; Marco Piatti; Benno Torgler (Fondazione Eni Enrico Mattei (FEEM), 2012)
This study investigates the citation patterns of theoretical and empirical papers over a period of almost 30 years, while also exploring the determinants of citation success. The results indicate that empirical papers attract more citation success than theoretical studies. However, the pattern over time is very similar with yearly mean citations peaking after around 4 years. Moreover, among empirical papers it appears that the cross-country studies are more successful than single country studies focusing on North America data or other regions.
Keywords: A11; B40; C0; N01; Z0; 330; Citations; Theory; Empirics; Cross-Country; North America